2015
DOI: 10.1088/0004-6256/150/4/115
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Star Formation Efficiency of the Dense Molecular Gas Across the Disks of Star-Forming Galaxies

Abstract: We present a new survey of HCN (1-0) emission, a tracer of dense molecular gas, focused on the littleexplored regime of normal star-forming galaxy disks. Combining HCN, CO, and infrared (IR) emission, we investigate the role of dense gas in star formation, finding systematic variations in both the apparent dense gas fraction (traced by the HCN-to-CO ratio) and the apparent star formation efficiency of dense gas (traced by the IR-to-HCN ratio). The latter may be unexpected, given the recent popularity of gas de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

87
346
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 181 publications
(439 citation statements)
references
References 75 publications
87
346
5
1
Order By: Relevance
“…Usero et al (2015) found SFE dense to depend on environment, being lower at high stellar surface densities and high molecular fractions Chen et al (2015) observed qualitatively similar behavior in their analysis of M51, noting that the IR-to-HCN ratio drops with decreasing radius in the galaxy.…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…Usero et al (2015) found SFE dense to depend on environment, being lower at high stellar surface densities and high molecular fractions Chen et al (2015) observed qualitatively similar behavior in their analysis of M51, noting that the IR-to-HCN ratio drops with decreasing radius in the galaxy.…”
Section: Resultssupporting
confidence: 54%
“…All data combined scatter about the ratio L TIR /L HCN ≈ 900 L ⊙ (K km s −1 pc 2 ) −1 (gray line; dashed lines show a factor of 3 scatter). (right) Zoom-in on data for the full-galaxy map of M51 and the pointings from Usero et al (2015). The typical uncertainty on the HCN luminosity for each line of sight is ∼ 10 5 K km s −1 pc 2 .…”
Section: Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, HCN could systematically overestimate the total dense gas mass present. We thus recommend that observations of HCN 1-0 in extreme environments should be checked for systematically weak emission due to self-absorption (e.g., via comparison with tracers like HC 3 N or CH 3 CN) before seeking a physical explanation for a lack of dense gas such as variations in the gas depletion time (e.g., García-Burillo et al 2012;Juneau et al 2009;Leroy et al 2015;Usero et al 2015). Such studies will also be important for determining whether the Galactic center conditions responsible for variations in the HCN 1-0 to dense gas conversion factor are actually relevant for other galaxies, or whether deviations from the Gao-Solomon relation in other systems are due to entirely separate effects that are a result of environments that are not sampled in our own Galaxy.…”
Section: Deriving Accurate Total Gas Masses From 3 MM Tracersmentioning
confidence: 99%